1996
DOI: 10.1021/ic950901m
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Indium(I) and Silver(I) Complexes of a Polyfluorinated Tris(pyrazolyl)borate

Abstract: A highly fluorinated tris(pyrazolyl)borate ligand has been used in the stabilization of a monomeric, In(I) species, [HB(3,5-(CF3)2Pz)3]In. The stability of [HB(3,5-(CF3)2Pz)3]In can be attributed primarily to the electronic effects of the fluorinated ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 16 publications
5
76
0
Order By: Relevance
“…Along these lines we have investigated the use of silver complex {HB[3,5-(CF 3 ) 2 Pz] 3 }Ag(THF) (1) containing the polyfluorinated and highly electron-withdrawing tris(pyrazolyl)borate ligand (Scheme 1). 1h, 8,9 Previous studies from our lab have demonstrated that this complex effectively functions as a carbene-transfer catalyst with diazoacetates serving as the precursor (Scheme 1). It has been found that this combination leads to addition to and subsequent rearrangement with aromatic systems (the Büchner reaction), 10 the formation and rearrangement of halonium ylides 11,12 and C-H insertion (Scheme 1).…”
mentioning
confidence: 99%
“…Along these lines we have investigated the use of silver complex {HB[3,5-(CF 3 ) 2 Pz] 3 }Ag(THF) (1) containing the polyfluorinated and highly electron-withdrawing tris(pyrazolyl)borate ligand (Scheme 1). 1h, 8,9 Previous studies from our lab have demonstrated that this complex effectively functions as a carbene-transfer catalyst with diazoacetates serving as the precursor (Scheme 1). It has been found that this combination leads to addition to and subsequent rearrangement with aromatic systems (the Büchner reaction), 10 the formation and rearrangement of halonium ylides 11,12 and C-H insertion (Scheme 1).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In addition, there are numerous spectroscopic investigations and computational studies of gold carbonyl adducts. 19 The chemistry of isolable species featuring bonds between gold(I) and unsaturated molecules such as CO, alkenes and alkynes (e.g., [HB (3,5- 6 ], Au(3-hexyne)Cl) [19][20][21][22][23][24] is an area of focus in our laboratory as they are rare, provide valuable fundamental information, and serve as useful models for reaction intermediates. 19 The chemistry of isolable species featuring bonds between gold(I) and unsaturated molecules such as CO, alkenes and alkynes (e.g., [HB (3,5- 6 ], Au(3-hexyne)Cl) [19][20][21][22][23][24] is an area of focus in our laboratory as they are rare, provide valuable fundamental information, and serve as useful models for reaction intermediates.…”
mentioning
confidence: 99%
“…This paper describes first efforts in that direction. In particular, we report the antimicrobial activity of silver(I) complexes bearing a highly fluorinated tris(pyrazolyl)borate [HB (3,5- corresponding sodium salt as described previously [28,29]. The dimethyl sulfoxide (OSMe 2 ) complex [HB(3,5-(CF 3 ) 2 Pz) 3 ] Ag(OSMe 2 ) can be obtained by treating [HB(3,5-(CF 3 ) 2 Pz) 3 ]Ag(THF) with OSMe 2 in hexane.…”
mentioning
confidence: 99%